Planning for the Implementation of Fine Motor Work Therapy Activities for Special Needs Pupils - Jasmon, Norashikin; Salubin, Mohd. Rosman (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
Occupational therapy activities can assist pupils with special needs in resolving some of their fine motor issues. Teachers should increase special needs pupils' pre-writing preparation with planned and structured activities that are methodical and have increasing qualities. This study aimed to observe how far Special Education teachers could go in planning appropriate activities based on their pupils' abilities by selecting occupational therapy activities and then sharing the potential impact expectations of fine motor ability of special needs pupils, particularly pupils with learning difficulties. This is a qualitative study that employs the hands-on method, observation, discussion, and interviews with 41 teachers and 17 pupil management assistants who participated in a continuous professional development course, which the researcher conducted at the Institute of Teacher Education Campus level and were able to produce a planning of activities that has the learned characteristics of advanced tolerance, focus, adaptability, and choosing the simplest to most complex occupational therapy activities. Furthermore, teachers can share the outcomes of activity planning and group discussion, as well as set expectations for the potential of the targeted pupils. Finally, this study suggests that special education teachers should collaborate and receive professionalism training on an ongoing basis to foster the proliferation of ideas and skills in planning appropriate activities to improve the fine motor skills of pupils with special needs.